Section Introduction: Games, Simulations and Emerging Technologies - Gibson, David; Ogata, H. (Springer, 2018)
This introduction to a section of the International Handbook of Information Technology in Primary and Secondary Education introduces concepts from educational data science that are central to researching and understanding games, simulations and emerging technologies. It then outlines briefly each of the chapters in the section.